The hard kind of promise - Willner-Pardo, Gina (Clarion Books / Houghton Mifflin Harcourt, 2010)
California seventh-graders Sarah and Marjorie made a promise in kindergarten to always be friends, but Marjorie is weird and Sarah, wanting to be at least somewhat popular, makes friends with a fellow choir member